644 Comparing the Use of Skin Clips and Tissue Adhesive in Wound Management After Renal Transplantation. (12th October 2021) - Caine, M; Bannon, A; Moinuddin, Z
Abstract: Introduction: Wound closure and dressing choice is a decision largely impacted by factors including surgeon preference and unit standard. This service improvement project aimed to assess the difference between skin clips, the current unit standard, and a tissue adhesive (Liquiband) after renal transplantation. Method: Data was collected retrospectively from July 2020 onwards. Outcome measures included the incidence of surgical site infections (SSI), cost, and nursing preference. Forty transplanted patients were selected, comprising the first twenty patients with skin clips and the first twenty patients with tissue adhesive. Medical notes and GP records were reviewed for any documented SSI or antibiotic prescription within six weeks of transplantation. A cost analysis was performed. Additionally, an online survey was distributed to nursing staff using Likert scales in response to a series of statements about wound care. Results: There were no documented SSIs in either group, and no patients commenced antibiotics for a wound infection. On average, there was a 45% cost saving when using tissue adhesive compared to skin clips and additional wound dressings. 100% of nurses strongly agreed or agreed that wound care was easier with tissue adhesive, and 93% agreed that considerably more time is spent on wound care for patients with skin clips. Conclusions: These results suggest that tissue adhesive offers comparable incidence of SSIs compared with skin clips. Furthermore, tissue adhesive is cheaper, more time-efficient, and preferred by nursing staff in post-operative wound care.